THE RELATIONSHIP BETWEEN JOB SATISFACTION AND WORK COMMITMENT: A PATHWAY TO EMPLOYEE RETENTION - Mansor, Farah Ahlami; Muhammad, Norrini; Hashim, Mimi Zazira; Mohd Firdaus Kozako, Intan Nurul ‘Ain; Omar, Siti Nur Zahirah (Journal of Islamic, Social, Economics and Development, 2024)
The purpose of this study was to investigate the relationship between job satisfaction and work commitment in private college in Kelantan. The objective of this research was to identify the significant relationship between employees' job satisfaction and work commitment. The researcher used the stratified random sampling technique because it was most appropriate in order to get the sample size from the population and used a questionnaire as the data instrument for the data collection. The sample size 127 are from six departments which academic department, information system department, administrative, finance, logistics and asset management department and human resources management department. The result of the finding is calculated by using the software IBM SPSS Version 22.0. The researcher ran descriptive statistics, normality tests and correlation coefficients. The result found that there is a significant positive and strong relationship between job satisfaction and work commitment. when organizations create a work environment that emphasizes job satisfaction through a supportive working environment, fair salary structure, meaningful work responsibilities, positive workplace relationships, and a platform for employees to voice their opinions, they can cultivate a highly committed workforce. It leads to improved employee retention, reduced turnover costs, and a more productive, stable, and high-performing organization. Organizations that invest in these areas are better positioned to retain top talent and build long-term success.